Incidence, risk factors and severity of retinopathy of prematurity in Turkey (TR-ROP study): a prospective, multicentre study in 69 neonatal intensive care units. Issue 12 (8th March 2018) - Bas, Ahmet Yagmur; Demirel, Nihal; Koc, Esin; Ulubas Isik, Dilek; Hirfanoglu, İbrahim Murat and Tunc, Turan
Abstract : Background: To evaluate the prevalence, risk factors and treatment of retinopathy of prematurity (ROP) in Turkey and to establish screening criteria for this condition. Methods: A prospective cohort study (TR-ROP) was performed between 1 April 2016 and 30 April 2017 in 69 neonatal intensive care units (NICUs). Infants with a birth weight (BW)≤1500 g or gestational age (GA)≤32 weeks and those with a BW>1500 g or GA>32 weeks with an unstable clinical course were included in the study. Predictors for the development of ROP were determined by logistic regression analyses. Results: The TR-ROP study included 6115 infants: 4964 (81%) with a GA≤32 weeks and 1151 (19%) with a GA>32 weeks. Overall, 27% had any stage of ROP and 6.7% had severe ROP. A lower BW, smaller GA, total days on oxygen, late-onset sepsis, frequency of red blood cell transfusions and relative weight gain were identified as independent risk factors for severe ROP in infants with a BW≤1500 g. Of all infants, 414 needed treatment and 395 (95.4%) of the treated infants had a BW≤1500 g. Sixty-six (16%) of the treated infants did not fulfil the Early Treatment for Retinopathy of Prematurity requirements for treatment. Conclusions: Screening of infants with a GA≤34 weeks or a BW<1700 g appears to be appropriate in Turkey. Monitoring standards of neonatal care and conducting quality improvement projects across the country are recommended to improve neonatal outcomes in Turkish NICUs. Trial registration number: NCT02814929, Results.